Molecular and isotopic evaluation of the maturation history of the organic matter in an Ordovician aquiclude (Michigan Basin): Evidence for late diagenetic biodegradation. (November 2018) - Jautzy, Josué J.; Ahad, Jason M.E.; Jensen, Mark; Clark, Ian D.
Highlights: A reconstruction of the Paleozoic maturation history of OM. Evidence for biodegradation of n -alkanes associated with microbial CH4 . Timing of OM biodegradation constrained as a late diagenetic event. Abstract: Previous characterization of a low permeability (10 −16  ≤ Kh  ≤ 10 −12 m s −1 ) and high salinity (> 5 M of Cl −, > 10× seawater salinity) aquiclude, in Upper Ordovician-aged sediments situated on the eastern flank of the Michigan Basin, where a deep geological repository for low and intermediate level nuclear waste is proposed, suggested a microbial origin for CH4 and CO2 based on their stable isotope values. CH4 is believed to have been produced and trapped during the Paleozoic in a relatively discrete and high organic matter (OM) horizon at the shale/carbonate transition. To further investigate the efficiency of confinement of this aquiclude, here we present detailed isotopic and geochemical stratigraphic profiles of OM and biomarkers, with the objective of understanding the origin of CH4 and its relative timing of confinement. Classical diagnostic ratios of polycyclic aromatic hydrocarbons, relative abundances of hopanes and degraded hopanes coupled to dual compound-specific isotopic analysis of n- alkanes, as well as δ 13 C analysis on different fractions of OM were measured. A partitioning of the Ordovician sedimentary succession into two systems is observed with an upper system that is self-sourced and confined, hosting the microbially derived CH4 with evidence of late diagenetic OM biodegradation and a lower system that reveals later secondary oil migration which has overprinted the organic geochemical record. We propose a conceptual model that would explain the generation and preservation of this paleo-bioreactor over time using the maturation history reconstruction derived from this dataset. This work not only provides essential field empirical evidence of a relationship between methanogenesis and late diagenetic biodegradation, but also shows the power of dual-compound-specific isotope analyses in deciphering between different maturation processes affecting OM in natural subsurface settings.